2021
DOI: 10.1159/000520006
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Oscillometric Measurement of Central Hemodynamics and Left Ventricular Hypertrophy in Hypertensive Patients

Abstract: <b><i>Introduction:</i></b> The augmentation index (AIx) or central systolic blood pressure (SBP), measured by radial applanation tonometry, has been reported to be independently associated with left ventricular hypertrophy (LVH) in Japanese hypertensive patients. Cuff-based oscillometric measurement of the AIx using Mobil-O-Graph® showed a low or moderate agreement with the AIx measurement with other devices. <b><i>Methods:</i></b> The AIx measured using the Mob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…However, opinion on the influence of cAIx@HR75 on LVH varies. In Obayashia's study ( 33 ), central AIx was lower in men than in women with hypertension, but the central AIx was not independently associated with the LVMI. It has been shown that in patients with never-treated hypertension, female sex, and shorter height are the important risk factors of elevated radial AIx 75 ( 34 ).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…However, opinion on the influence of cAIx@HR75 on LVH varies. In Obayashia's study ( 33 ), central AIx was lower in men than in women with hypertension, but the central AIx was not independently associated with the LVMI. It has been shown that in patients with never-treated hypertension, female sex, and shorter height are the important risk factors of elevated radial AIx 75 ( 34 ).…”
Section: Discussionmentioning
confidence: 83%
“…However, multiple logistical regression with age stratified by 60 years showed that cAIx@HR75 was not significantly associated with LVH. Aix was associated with arterial stiffness; however, it has been shown that central SBP, but not the central AIx, was an independent determinant of LVH in hypertensive patients in general ( 33 ). Further research needs to be conducted to explore the varying relationship of cAIx@HR75 and LVH.…”
Section: Discussionmentioning
confidence: 99%
“…The main descriptive characteristics of the studies that have been included in the meta-analysis are described in Tables 1 through 4 per PWRs biomarker AIx, AP, Pb, RI, respectively. Out of the 17 identified studies on AIx (Table 1), 13 studies [25][26][27][28][29][30][31][32][33][34][35][36][37] with overall 5799 participants assessed AIx at the level of central arteries (either the carotid artery or the aorta) and 4 studies [38][39][40][41] with overall 993 participants assessed AIx at the peripheral arteries (either the radial artery or the finger). Carotid AIx was more often assessed, overall, in 7 studies 26,[31][32][33][34][35][36] with overall 3331 participants using local carotid pulse wave recording with either applanation tonometry (k=6, n=3129, 4 different recording systems were identified) 26,[31][32][33][34][35] or ultrasonography (k=1, n=202).…”
Section: Data On Lvhmentioning
confidence: 99%
“…Carotid AIx was more often assessed, overall, in 7 studies 26,[31][32][33][34][35][36] with overall 3331 participants using local carotid pulse wave recording with either applanation tonometry (k=6, n=3129, 4 different recording systems were identified) 26,[31][32][33][34][35] or ultrasonography (k=1, n=202). 36 Aortic AIx was assessed in 6 studies 25,[27][28][29][30]37 38,39,41 with overall 553 participants with the use of radial applanation tonometry and PWA using in all cases the HEM-9000/9010AI (Omron Healthcare Co. Ltd, Kyoto, Japan) device. Patients with paroxysmal atrial fibrillation were included as subgroup in 2 studies 28,39 ; all subjects were in sinus rhythm at the time the AIx was measured.…”
Section: Data On Lvhmentioning
confidence: 99%
See 1 more Smart Citation